Analisis Implementasi Kurikulum Merdeka pada Pembelajaran Matematika Berdiferensiasi di SMP Negeri 01 Abung Barat - Syarifah, Annisa Jamil; Anggoro, Bambang Sri; Andriani, Siska (Universitas Nusantara PGRI Kediri, 2025)
Differentiated learning is a learning process that accomodates students to learn according to their abilities and respective interest. The aims of this research is to describe the differentiated mathematics learning process in the independent curriculum and to describe the mathematics learning outcomes of students who receive differentiated learning. The method used in the descriptive research with qualitative analysis and the location in this study was to take place at SMP Negeri 01 Abung Barat with principals, math teacher, and three students as informants. The results in this study are the process of implemented differentiated mathematics learning is carried out by implemented a process and product differentiation strategy based on the leaning needs and interests of different students. Students learning outcomes that are overall student scores in three classes have reached the KKM and many student’s scores have even exceeded the KKM. This proves that there is an increase in the scores of students who have received differentiated mathematics learning.